2019
DOI: 10.31486/toj.18.0117
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printed Patient Models for Complex Pediatric Spinal Surgery

Abstract: Background: Pediatric spinal deformity surgeries are challenging operations that require considerable expertise and resources. The unique anatomy and rarity of these cases present challenges in surgical training and preparation. We present a case series illustrating how 3-dimensional (3-D) printed models were used in preoperative planning for 3 cases of pediatric spinal deformity surgery. Case Series: Patient 1 was a 6-year-old male with scoliosis secondary to an L3 hemivertebra and severe congenital heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In line with our observations, it has been shown recently that preoperative planning with 3D modeling and printing can improve the accuracy of screw positioning and provide an improved sense of spinal anatomy [6], especially in the treatment of spinal deformity in children [7]. Even though most papers address the value of 3D-printed models for anatomical considerations [6, 7, 17-19], they do not explore the full potential of preoperative in vitro testing. Our case shows that testing on a 3D-printed model in vitro not only improves visualization and the sense of spinal anatomy and screw positioning but also offers additional opportunities to find the best surgical solutions and test the feasibility of fixation in the pediatric spine preoperatively, thereby reducing intraoperative complications, especially in the absence of intraoperative navigation.…”
Section: Discussionsupporting
confidence: 54%
“…In line with our observations, it has been shown recently that preoperative planning with 3D modeling and printing can improve the accuracy of screw positioning and provide an improved sense of spinal anatomy [6], especially in the treatment of spinal deformity in children [7]. Even though most papers address the value of 3D-printed models for anatomical considerations [6, 7, 17-19], they do not explore the full potential of preoperative in vitro testing. Our case shows that testing on a 3D-printed model in vitro not only improves visualization and the sense of spinal anatomy and screw positioning but also offers additional opportunities to find the best surgical solutions and test the feasibility of fixation in the pediatric spine preoperatively, thereby reducing intraoperative complications, especially in the absence of intraoperative navigation.…”
Section: Discussionsupporting
confidence: 54%
“…Applications include prosthetics, 4,5 anatomical models for surgical planning, 6,7 and education 8‐13 . The ability of AM to produce highly customized anatomical models that can not only be visualized but also manipulated in three dimensions by touch has shown promise as a valuable tool in diverse medical fields ranging from neurosurgery, 14,15 orthopedics, 16,17 otolaryngology, 18 and cardiothoracic surgery 19 . These devices and models can often be printed directly from, or in concert with, computed tomography (CT) images of patient anatomy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many studies have indicated that 3DP spine model could promote surgical education, team communication and patient understanding. [34][35][36][37] In conclusion, it is worthwile to apply the 3DP technology in severe spinal deformity surgery concerning the following advantages. Firstly, 3DP spine model improves the understanding of the anatomical structure of the surgical site and can be used for surgical rehearsal to accelerate the learning curve of surgeons and improve the quality of clinical education.…”
Section: Discussionmentioning
confidence: 99%